Effect Of Green Marketing And Brand Image On Purchase Decision Of Aqua Gallon With Customer Loyalty As A Mediating Variable - Araujo, Delia Iria Magno de; Ximenes, Elias; Mujanah, Siti; Halik, Abdul (Sean Institute, 2025)
This study aims to analyze the influence of brand image and green marketing on purchasing decisions for Aqua Galon products with consumer loyalty as a mediating variable. This study is an explanatory research type, sampling using nonprobability sampling techniques. Data were taken by distributing questionnaires directly to 100 respondents of consumers of AQUA gallon packaging products in Jabodetabek. Data were collected through a survey of Aqua consumers and analyzed using the Structural Equation Modeling (SEM) method. The results of the study indicate that brand image has a very significant and positive influence on purchasing decisions and consumer loyalty. Green marketing also has a significant effect on consumer loyalty, but its impact on purchasing decisions is relatively small compared to brand image. In addition, consumer loyalty does not have a significant effect on purchasing decisions and does not act as a mediating variable between brand image and purchasing decisions or between green marketing and purchasing decisions. These findings indicate that to improve purchasing decisions, companies need to focus more on improving brand image, while green marketing strategies can be used to build consumer loyalty. This conclusion provides important implications for companies in designing effective marketing strategies to strengthen brand positions in the market and increase consumer loyalty without expecting loyalty to directly drive purchasing decisions.